Gender differences in residential mobility: The case of leaving home in East Germany - Ferdinand Geissler; Thomas Leopold; Sebastian Pink (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
This paper investigates gender differences in the spatial mobility of young adults when initially leaving their parental home. Using individual data from 11 waves (2000-2010) of the SOEP, we examine whether female home leavers in East Germany move across greater distances than males and whether these differences are explained by the gender gap in education. Our results reveal that female home leavers in East Germany are exceptionally mobile. This effect is attributable to their higher propensity of moving to West Germany. Education does not explain these gender differences.
Keywords: C23; J61; R23; 330; Jugendliche; Binnenwanderung; Geschlecht; Bildungsniveau; Neue Bundesländer